SOFT POWER: THE MEANS TO SUCCESS IN WORLD POLITICS - Yodgorova Zebo (Ta'lim innovatsiyasi va integratsiyasi, 2025)
One of the most influential books I have ever read is Joseph Nye’s “Soft Power: The means to success in World Politics”. The book that fundamentally changed my views on international relations and diplomacy. Before reading this book, I had not fully grasped the essence of soft power, but the book greatly helped me to gain a better understanding of its concept. This book fundamentally reshaped my understanding of power, influence, and leadership in a globalized world. Nye’s concept of "soft power," which emphasizes the ability to shape others’ preferences through attraction rather than coercion or payment, resonated deeply with me, not only in the context of international relations but also in understanding human interaction and societal change. It taught me that influence is not always about control but often about creating shared values, trust, and mutual respect.